PENGARUH KINERJA KEUANGAN TERHADAP KUALITAS INFORMASI INTERNET FINANCIAL REPORTING DENGAN KEPEMILIKAN SAHAM PUBLIK SEBAGAI VARIABEL MODERASI - Gunawan, Andrew (LPPM STIE Pertiba, 2019)
This study aims to test empirically whether public share ownership is able to moderate the relationship between the financial performance proxyed with profitabiltas on the quality of information. The quality of IFR information is measured through the disclosure index compiled by Boubaker et al (2012). This index contains 100 items of website-based disclosure that are commonly used in measuring the quality of accounting-based reporting information. The sample of this study is a manufacturing company listed on the Indonesia Stock Exchange, where the data analysis techniques that will be used are moderated Regresion Analysis with the help of Indirect macro created by Andrew F. Hayes (2015) in combination with SPSS 23. The results show that public shareholding is able moderate the relationship between financial performance with the quality of IFR information.